The Clash of Indian Cultural Identity in a European Environment in the Film Mrs. Chatterjee vs Norway - MF. Rani Shinta Hapsari (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
The film Mrs. Chatterjee vs Norway portrays the complexity of cultural clashes experienced by the Indian diaspora when confronted with the European legal system. This study aims at analyzing the representation of Indian and Norwegian cultural identity clashes and the process of self-negotiation experienced by the main character. Using a descriptive qualitative method with Stuart Hall's Cultural Identity theory as a lens of analysis on the concepts of identity as being and identity as becoming, this study dissects the narrative and cinematic elements of the film. The findings show that the character Mrs. Chatterjee initially maintained a strong identity as being through traditional cultural practices, which were later criminalized by Norwegian child welfare standards. This systemic pressure forces the character to transform towards identity as becoming by adopting Western assertiveness and legal logic to fight injustice, affirming that identity in the diaspora is a dynamic construction that is constantly negotiated amid unequal power relations.